Correlation of Urinary Collagen IV: Urinary Albumin Ratio in the Prediction of Preeclampsia - Ul-Hosna, Asma; Shahid, Asma Rumanaz; Bhuyan, AKM Mohiuddin; Thamina, Hosna Zari; Salman, Mohammad; Sultan, Md Ashraf Uddin; Akhter, Shapla (University Heart Journal, 2010)
The purpose of this study was to assess the value of MA in the prediction of PE and also to compare urinary collagen IV with MA in this prediction. A total of 200 subjects (age 25±4 years, M±SC), were selected in their early pregnancy (10 to 14 weeks). Blood glucose, serum lipids, serum and urinary creatinine, urinary albumin and urinary collagen IV were measured in these subjects and they were followed up to the term for the possible development of PE, MA was defined by albumin creatinine ratio (ACR) above 32mg/g and high urinary collagen IV was defined by values above the cut-off point 2.54 ng/ml determined by the median value of the controls. The data were analyzed by grouping the subjects who developed PE in later stages of pregnancy (the PE group) and those who did not develop PE in later stages (the control group). Out of 200 subjects 94 were primigravida and 106 were multigravida. From the total subjects 16 developed PE, which shows a prevalence of about 8.4%. The PE group showed a relatively higher value of ACR as compared to control group. 106 subjects had MA out of which 13 developed PE. The sensitivity of ACR in predicting the development of PE was 80%, specificity 49.54%, PPV 12.69% and NPV 96.42%. Regarding urinary collagen IV the PE group showed no significant difference with the value of the control group. 103 subjects had high urinary collagen IV and out of them 11 developed PE. The sensitivity of high urinary collagen IV in prediction PE was found to have no significant difference with ACR in this respect. The data suggest the following conclusions: Early pregnancy levels of microalbuminuria and urinary collagen IV can be used as predictors of PE with high negative value. Urinary collagen IV has no added advantage over MA in this respect. Keywords : MA-Micro DOI: 10.3329/uhj.v5i2.4555 University Heart Journal Vol.5(2) July 2009 pp.59-62